the PHENOMENON OF CODE MIXING ADN CODE SWITCHING IN FACEBOOK USER STATUS - Afif Kholisun Nashoih (JoEMS (Journal of Education and Management Studies), 2019)
The occurrence of code mixing and code switching in Indonesian is a result of bilingualism by people who do have their own regional languages, and the presence of foreign language interventions. This is interesting to study so that it can be described how mixed use and code switching in life is socializing. The collection of research data was taken by the authors of the Facebook status of students who were working in the academic world. From the results of the analysis, it can be concluded that the most frequently used code mix is ​​in the form of words, and all of them are spoken in a variety of non-standard languages. The use of this mixed code is motivated by the factors of mother tongue (Javanese) and the surrounding language environment. Therefore this code mix is ​​dominated by a mixture of Javanese. While the code switching that is often used comes from foreign languages ​​both Arabic and English. the negative impact of code mixing and code switching is the loss of the characteristics and identity of Indonesian as a national language. In addition, it also triggers the assimilation of language which will later result in the extinction of the language.